2020
DOI: 10.5888/pcd17.190359
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Polypharmacy and Quality of Life Among People in 24 Countries Living With HIV

Abstract: What is already known on this topic? People living with HIV (PLHIV) have greater incidence of comorbidities and higher prevalence of polypharmacy, most commonly defined as taking 5 or more medications concurrently, than the general population. What is added by this study? PLHIV reporting polypharmacy had significantly worse overall health outcomes, including significantly lower prevalence of self-reported virologic control and treatment satisfaction. These findings were significant despite controlling for pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 20 publications
3
40
0
Order By: Relevance
“…The percentage of PLHIV with suboptimal adherence in our study (23.8%) is very close to the 24.1% overall estimate reported in a recent multi-country study 12 . Another study by Okoli et al 36 found that 66.6% of PLHIV worried about the long-term effects of HIV medicines, similar to 63.4% in our study. That same study reported that 18.6% (288/1550) of those who ever switched ART (or 13.6% [288/2112] of all study participants) reported switching because of drug-drug interactions; in our study, 15.4% of all participants reported ever changing ART because of drug-drug interactions.…”
Section: Discussionsupporting
confidence: 89%
“…The percentage of PLHIV with suboptimal adherence in our study (23.8%) is very close to the 24.1% overall estimate reported in a recent multi-country study 12 . Another study by Okoli et al 36 found that 66.6% of PLHIV worried about the long-term effects of HIV medicines, similar to 63.4% in our study. That same study reported that 18.6% (288/1550) of those who ever switched ART (or 13.6% [288/2112] of all study participants) reported switching because of drug-drug interactions; in our study, 15.4% of all participants reported ever changing ART because of drug-drug interactions.…”
Section: Discussionsupporting
confidence: 89%
“…We previously reported the percentage of PLHIV open to HIV treatments composed of fewer medicines in preliminary analyses of our data from 24 countries. 24 Here we provide an update of that estimate based on the full sample of 25 countries, along with additional multivariable analyses.…”
Section: Treatment Aspirationsmentioning
confidence: 99%
“…Inclusion criteria were men and women aged ≥ 18 years who were diagnosed with HIV and on antiretroviral therapy (ART); a total of 2389 PLHIV aged 19–86 years participated. The study methodology has been previously reported [ 11 ]. Participants were recruited using targeted and snowball sampling approaches across multiple platforms and in collaboration with multiple HIV organizations; responses were collected over the web or in-person.…”
Section: Methodsmentioning
confidence: 99%
“…As treatment is lifelong, many PLHIV start their therapy soon after diagnosis and once they become undetectable continue this treatment without review for some time, however as their lives evolve when living with HIV, needs may change and newer treatments may emerge that could benefit them. More so, as PLHIV age and develop co-morbidities, new treatment-related challenges may arise, especially if they experience polypharmacy [ 11 ]. More discussions between patients and HCPs may be needed in such situations; a review of treatment decisions may also be necessary, even in the absence of treatment failure, to optimize care, reduce the risk of drug toxicities, and improve quality of life.…”
Section: Introductionmentioning
confidence: 99%